Nonhomogeneous distribution of human immunodeficiency virus type 1 proviruses in the spleen. - Delassus, S (1992)
A nonhomogeneous spatial distribution of human immunodeficiency virus type 1 proviruses in an infected spleen was observed. Antigenic stimulation of infected cells might explain this partition.